MODEL KOPERASI PESANTREN DAN KEMANDIRIAN EKONOMI : STUDI KOPONTREN AL-IKHLAS MAGETAN JAWA TIMUR - Hamdani, Hamdani (Investama : Jurnal Ekonomi dan Bisnis, 2024)
This study aims to examine the management of the Al-Ikhlas Islamic boarding school cooperative in Krakas, Magetan, East Java, in managing santri-based finances. This cooperative carries an inclusive model with the principle of "from santri, by santri, and for santri", and prohibits trading activities outside the cooperative within the pesantren environment. With the number of santri reaching 600 people, the cooperative is able to generate a daily turnover of up to IDR 30 million from transactions for the daily needs of santri. This study shows that the pesantren cooperative not only supports internal economic activities, but also becomes an important instrument in creating economic independence, forming the entrepreneurial character of santri, and covering the operational costs of the pesantren. This model proves that pesantren-based cooperatives can be a solution to the economic challenges of religious institutions and surrounding communities, as well as contributing to the development of a people's economy based on sharia values.